CORRELATION AND PRINCIPAL COMPONENT ANALYSIS FOR YIELD-RELATED AND PHYSIOLOGICAL TRAITS UNDER HEAT STRESS IN GROUNDNUT (Arachis hypogaea L.) - S. NARENDER REDDY and V. ANIL KUMAR, B. RACHANA, K. ESWARI, S. SUDHEER KUMAR (The Journal of Research, PJTSAU, 2023)
The present investigation was carried out to study the relationship between yield-related and physiological traits under heat stress in groundnut. This experiment was conducted with a set of sixty-four groundnut genotypes at two dates of sowing during summer 2020-21 at International crops research institute for semi-arid tropics (ICRISAT), Patancheru, India. Observations were recorded on eleven traits days to 50% flowering, plant height, no of primary branches, pod yield per plant, kernel yield per plant, hundred kernel weight, shelling percentage, total biomass, harvest index, SPAD chlorophyll meter reading and membrane thermo-stability. The results of correlation analysis revealed that pod yield was positively associated with kernel yield, harvestindex, biomass and SPAD chlorophyll meter reading in both environments, suggesting their role indirect selection for improvementin yield. Principal component analysis showed that four principal components explained the maximum variability of 67.57% and68.52% in first date of sowing (S1) and second date of sowing (S2) environments respectively. Kernel yield per plant, pod yield perplant, and harvest index contributed for maximum variation of 26% with first principal component in both environments. These traits are significant to identify/develop heat-resilient varieties, as they contributed maximum towards the divergence of groundnut genotypes.